Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

Nanoconfinement of Prussian blue ionic liquid-MOF nanocrystal material for cesium adsorption - Shuang-Long Wang; Yue-Ru Zhou; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2026)

Comprehensive low-damage mechanical weeding technology considering the spatial distribution of crop roots: A case study of maize farmland - Deng Sun; Longzhe Quan; Zhaoxia Lou; Guoxiang Zhang; Chen Ru; Xiaojie Li; Zhiming Guo; Jinbin He; Chuan Wang; Yongheng Wang (Computers and Electronics in Agriculture, 2026)

From coal gasification slag-derived water glass to monodisperse silica sol: Silicate-species evolution and particle-growth mechanisms - Ru Guo; Jianbo Zhang; Yiyang Li; Hongxiang Xu; Zhengping Zuo; Zhiming Sun; Shaopeng Li; Huiquan Li (Journal of Environmental Chemical Engineering, 2026)

Lattice carbon-induced electronic regulation of AlCo2O4 spinels for boosting toluene oxidation - Dadao Wang; Xueqin Yang; Mimi Wu; Menglan Xiao; Yanhu Zhang; Mianmian Zhang; Xiuhong Zhu; Guangxin Ru; Yucong Guo; Bo Shi; Xiaolin Yu; Maofa Ge (Journal of Environmental Chemical Engineering, 2026)

Structural and functional responses of myofibrillar proteins from yellow croaker to plasma-activated buffer: evidence from a simulated PAW system - Fangqi Yuan; Quanyou Guo; Zuofeng Shi; Huawei Wu; Wenge Yang; Tao Huang; Ru Jia; Huamao Wei (Food Research International, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Novel temperature-tolerant Schiff base derivative as high-efficiency inhibitor for acid corrosion of N80 steel - Li-Mao Chen; Shuang-Jian Li; Ru-Han Li; Bo-Kai Liao; Xing-Peng Guo; Long-Fei Song (Chemical Engineering Journal, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Differential host choices of Helicoverpa armigera and H. assulta to tomato - Jie-Wen Mao; Qian-Wen Luo; Shao-Ting Duan; Meng-Hao Zhang; Xiao-Guang Liu; Xian-Ru Guo; Yan-Min Liu; Wei-Zheng Li (Arthropod-Plant Interactions, 2026)

Analyzing phosphorus flow in crop production via interpretable machine learning: Insights from a typical agricultural region of Jiangxi Province, China - Yuejin Chen; Wending Huang; Lele Ru; Shuhui Peng; Wuhu Guo; Evgeny Abakumov; Ekaterina Chebykina; Yalan Zhang; Zanxu Chen; Dan Wang; Shijie Dai; Yanqi Liu; et al. (Applied Geochemistry, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Prior-guided multi-domain mixture-of-experts for multimodal Earth observation data gaps - Chuang Liu; Jianhua Guo; Yingdong Pi; Xiao Wu; Zhiqi Zhang; Ru Chen; Xinyi Wang; Mi Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

A core innate immune gene panel derived from germ-free larval zebrafish transcriptomics resolves strain-specific induction by Aeromonas veronii and Lacticaseibacillus rhamnosus GG - Xiang-Ru Liu; Ying Liu; Chen-Cong Zhang; Zi-Shu Huang; Feng-Yi Guo; De-Sheng Pei (Fish & Shellfish Immunology, 2026)

Diniconazole leads to neurotoxicity in zebrafish via triggering TLR4/MyD88-mediated immune-inflammatory responses - Hongying Zhang; Ru Guo; Youjuan Wu; Jiajun Huang; Zijia Yin; Kaiwen Zhao; Xuefeng Liu; Meifeng Li; Zeyin Jiang; Shanghong Wang; Lihua Fan; Chengyu Hu; et al. (Fish & Shellfish Immunology, 2026)

Shape-memory effect in a flexible hydrogen-bonded organic framework for efficient C2H2/CO2 separation - Chunchen Gao; He Zheng; Wenjie Chen; Yiting Guo; Ru Xu; Ziyi Luo; Qifeng Luo; Xingliang Nie; Xin Lian; Xiongli Liu; Yabing He; Lin Li; et al. (Chemical Engineering Journal, 2026)

Facial width-to-height ratio predicts aggression and contest outcomes in wild golden snub-nosed monkeys - Pei Zhang; Yan-Ni La; Fei Niu; Jin-Bang Zhang; Paul A. Garber; Derek W. Dunn; Ru-Liang Pan; Kang Huang; Bao-Guo Li (Animal Behaviour, 2026)

Four typical N2O emission regimes in temperate monsoon-type urban rivers unraveled via quantified microbial sources under coupled natural hydrological and anthropogenic perturbations - Shuo Wang; Shengjie Li; Yiru Chen; Zhengzhu Dang; Ru Guo; Xianfang Zhu; Wei Zhi; Guodong Ji (Water Research, 2026)

Paedocin A: An undescribed iridoid with a C1-C4 ether linkage from Paederia foetida with hepatoprotective effects - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry Letters, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Changes in source-specific health risks of PM2.5-bound trace elements after the residential “coal-to-gas” conversion measure in urban Beijing - Wei Yuan; Ru-Jin Huang; Jing Duan; Jie Guo; Wenjuan Cao; Ting Wang; Jingye Ren; Yanan Zhan; Wei Xu (Journal of Environmental Sciences, 2026)

Stable leaf pH of grassland community under nitrogen inputs ensured by contrasting intra- and inter-specific variations - Xiao-Hua Yang; Cong Ding; Xiao-Sa Liang; Yuan-Xiu Wu; Xiao-Ru Zhang; Xiao-Jing Zhang; Liang-Chao Jiang; Xing-Guo Han; Xiao-Tao Lü (Plant and Soil, 2026)

The SP1/NEDD4L Axis Suppresses the Breast Cancer Progression by Downregulating SNAI2 Expression - Baile Zuo; Xiaoyan Li; Mengke Wang; Zhuoya Yin; Yifan Guo; Liping Zhao; Ru Yang; Binghua Tong; Zhenni Guo; Meiqing Sun; Jin Zhao; Huina Zhang; et al. (Biochemical Genetics, 2026)

Ozone-mediated microbial succession and kinetic for refrigerated grass carp (Ctenopharyngodon idella) fillets - Cheng Guo; Guodong Xu; Shanbai Xiong; Tao Yin; Ru Liu; Juan You (International Journal of Food Microbiology, 2026)

Shifting carbon emission dominance across subway lifecycle phases: A refined subsystem-interaction assessment - Jing Pu; Chen Cai; Shijun Chen; Ru Guo; Ruimin Lin; Xingyu Ding; Jia Liu; Kaiming Peng; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Capacity prediction of cobalt nickel phosphide supercapacitors based on machine learning - Qiang Shen; Licheng Zhu; Zhibo Shen; Tianzeng Ru; Minghui Guo; Jun Ren; Tao Wu; Zhanqiang Liu (Chemical Engineering Journal, 2026)

Knowledge-infused hierarchical causal inference framework for decoding sludge settleability to quantitatively regulate multi-process wastewater treatment - Yucheng Li; Chen Cai; Feiyun Sun; Xiangfeng Huang; Kaiming Peng; Ru Guo; Jia Liu (Bioresource Technology, 2026)

Mobility heterogeneity influences the relationship between built environment and metro travel emissions - Jing Pu; Chen Cai; Wei Zhu; Quan Yuan; Ru Guo; Xingyu Ding; Jia Liu; Kaiming Peng; Yanei Xue; Xiangfeng Huang (Transportation Research Part D: Transport and Environment, 2026)

Wavelength-tunable light regulates binding affinity of histone deacetylase inhibitors via azobenzene Photoswitches - Yifan Ru; Sifan Guo; Yu He; Xiujuan Huang; Zhenguo Zhang; Lei Shi; Xiaoguang Shao; Zhong Li; Wen Fu; Xusheng Shao (Pesticide Biochemistry and Physiology, 2026)

Mechanisms of flow-induced noise and control in underwater grille-cavity systems: Effects of grille number and inclination - Qing-Shuang Zhang; Yong-Liang Xiong; Ru-Nan Hua; Guo-Cang Sun; Dan Yang (Ocean Engineering, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Effects of Different Chemical Fertilizer Strategies on Rhizosphere Soil Bacterial Diversity and Community Structure in Legume-grass Intercropping Systems - Jing-ru Chen; Xiao-shan Chen; Li-li Nan; Quan-en Guo (Journal of Soil Science and Plant Nutrition, 2026)

Unlocking the health co-benefits of the low-carbon transition: evidence from wind and solar power deployment in China - Ru Li; Yan Guo; Chen Zhang (Mitigation and Adaptation Strategies for Global Change, 2026)

A novel index for the comprehensive assessment of competitive relationships in maize–weed communities using UAV-based hyperspectral data - Caixia Wang; Longzhe Quan; Fei Wang; Jian Xu; Guoxiang Zhang; Xiaojie Li; Chen Ru; Zhaoxia Lou; Chuan Wang; Zhiming Guo (Computers and Electronics in Agriculture, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Editor's note “Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPAR/NF-B signaling” [Sci. Total Enviro. 881 (2023) 163430] - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2026)

A 2000-year record of polycyclic aromatic hydrocarbon deposition in Lake Basongcuo, southeast Tibet: Source apportionment and implications for human impacts - Ru Guo; Jinglu Wu; Jianchao Zhou; Miao Jin (Journal of Environmental Management, 2026)

Co-gasification coupled with steam reforming of inseparable livestock biowastes for green hydrogen-rich syngas production - Jiarui Zhu; Qiuhan Pu; Liang Wang; Ge Kong; Zengjian Guo; Ru Sun; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Tailoring food-grade Pickering emulsions through advanced particle design: a comprehensive review - Han Ru; Mingyao Zhu; Fei Luan; Yajun Shi; Xiaofei Zhang; Dongyan Guo; Bingtao Zhai; Dingkun Zhang; Junbo Zou (Food Chemistry, 2026)

Distinguishing the contributions of organic matter and iron (oxyhydr)oxides to zinc availability in paddy soils surrounding lead-zinc mines - Yecheng Li; Zebin Hong; Yan Ru; Guojun Chen; Xiaomin Li; Shiwen Hu; Yang Yang; Chao Guo; Shan Wang; Pengfei Cheng; Qi Wang; Tongxu Liu (Environmental Pollution, 2026)

Assessing synergy of CO2 and pollutant reductions in industrial parks from the industrial chain perspective - Shenghua Yan; Chen Cai; Jia Liu; Kaiming Peng; Ru Guo; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Highly sensitive ppb-level high-entropy metal oxide gas sensor with temperature-dependent dual-selectivity for Ammonia and Triethylamine - Ru Wang; Guozheng Zhu; Yutong Guo; Yilin Du; Mengran Ran; Yuxin Cao; Hongmin Zhu; Fanli Meng; Yong Zhao (Chemical Engineering Journal, 2026)

Efficient Biosynthesis of Selenium-Enriched Saccharomyces cerevisiae via Siderophore-Assisted selenite uptake and biotransformation - Wen-tao Du; Ya-ru Wei; Xue Zhao; Qiang-qiang Gou; Omer Hassan Ali; Wen-di Wang; Jia-nan Xu; Zai-ping Feng; Xin-guo Zhang (Bioresource Technology, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Causal-informed domain adaptation with cross-attention for predicting anomalous effluent quality fluctuations in wastewater treatment plants - Hanxin Zhang; Haiping Zhang; Jia Liu; Kaiming Peng; Ru Guo; Feiyun Sun; Xiangfeng Huang; Chen Cai (Water Research, 2026)

Cyclopentanoid monoterpene glycosides from the aerial parts of Paederia foetida L - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Bridging Aquaculture and Human Medicine: A Comprehensive Review of Zebrafish Models for Chronic Kidney Disease - Feng‐Yi Guo; Hao‐Yu Yang; Lan‐Chen Zhang; Xiang‐Ru Liu; Pan‐Pan Jia; De‐Sheng Pei (Reviews in Aquaculture, 2026)
Chronic kidney disease (CKD) poses a significant global health burden, necessitating robust animal models for mechanistic studies and drug discovery. Zebrafish offers unique advantages as a powerful models in kidney disease, including high‐throughput compatibility, optical transparency, and significant genetic and nephron homology with both humans and farmed teleosts. However, challenges, such as the species' potent regenerative capacity and a lack of standardized diagnostic thresholds, hinder their broad application. This review systematically summarizes four principal induction strategies: environmental stress, nephrotoxic chemical exposure, CRISPR/Cas‐based gene editing, and transgenesis. We further outline a validation pipeline that integrates functional assays, morphometrics, and histopathology, while advocating for cross‐laboratory harmonization. Additionally, we compare risk factors for CKD and CKD of unknown etiology (CKDu), emphasizing environmental contributors. Collectively, we propose zebrafish as a reproducible platform for aquaculture applications, specifically for nephropathy early‐warning systems and functional feed assessment, and for human therapeutic research. These standardized models hold great promise for high‐throughput drug screening and elucidating disease mechanisms, facilitating the translation of findings to both aquaculture and clinical medicine.

Construction of lignin crosslinked nanocellulose 3D-printed solar evaporators for efficient seawater desalination via hydroxyl-yne click chemistry - Juan Yu; Xinyi Zhu; Ru Guo; Bowen Li; Liqin Jiang; Zhiguo Wang; Yimin Fan (Carbohydrate Polymers, 2026)

Mechanisms and Scenario Predictions of the Digital Economy’s Impact on Pollution and Carbon Emission Reduction: A Case Study of the Yellow River Basin in China - Tianle Shi; Zhengmeng Hou; Jianhua Liu; Hao Fang; Qichen Wang; Yilin Guo; Ru Zhang; Liangchao Huang (International Journal of Environmental Research, 2026)
This study investigates how the digital economy reduces pollution and carbon emissions (RPCE) in the Yellow River Basin through three core mechanisms: (1) enabling real-time environmental monitoring and precision regulation, (2) fostering enterprise green production via digital transformation, and (3) driving technological innovation and industrial upgrading, proposing three testable hypotheses on these pathways. Indicators for the digital economy and RPCE are developed, and a spatiotemporal analysis of RPCE levels is conducted at both the municipal and grid scales. Employing the STIRPAT (Stochastic Impacts by Regression on Population, Affluence, and Technology) model to comprehensively examine population, affluence, and technology drivers, and innovatively integrating analysis at both municipal and grid scales to overcome traditional limitations, this study examines the direct and mediating effects of the digital economy on RPCE, along with heterogeneity analysis, endogeneity discussions, and exogenous shock tests, providing a more refined framework for revealing the mechanisms. Based on empirical findings, future RPCE trends in the basin are projected, with a proposed three-pronged strategy: digital infrastructure deployment, sector-specific interventions, and place-based prioritization (technology-upgrading midstream; clean-energy transition upstream). The main conclusions are as follows: (1) During the study period, RPCE in the Yellow River Basin showed significant improvement, with an upstream > downstream > midstream pattern and a block-like distribution. (2) The statistically significant regression coefficient (β = -0.476, p < 0.01) indicates a positive impact of the digital economy on RPCE, thus validating Hypothesis 1. Both technological innovation and industrial structure upgrading serve as positive mediators in the influence of the digital economy on RPCE, confirming Hypotheses 2 and Hypotheses 3. (3) The growth rate of population size is a major factor driving divergence in the RPCE index across the basin. To advance RPCE in the Yellow River Basin, policies should prioritize the development of the digital economy while promoting high-quality economic growth and stabilizing population growth rates.

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Lanthanum-quaternized chitosan-modified zeolite for long-lasting operation of constructed wetland: A bifunctional strategy for simultaneous phosphorus removal and microbial clogging mitigation - Ling Wang; Jian-Guo Zhang; Hong-Yin Sha; Yi-Ru Wang; Hao-Yu Wang; Guang-Can Zhu; Yong-Ze Lu (Water Research, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Effects of nighttime warming and nitrogen addition on phytoplankton biomass in a submerged macrophytes-dominated freshwater wetland - Yaru Lyu; Jiayin Feng; Wenjing Ma; Chao Wang; Mengyu Yan; Zixuan Yang; Yunpeng Guo; Jinhua Zhang; Hongpeng Wang; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Journal of Environmental Sciences, 2026)

Aging enhancement and synergistic effect on toxicity to soil fauna by polystyrene microplastics-tetrabromobisphenol A toxicity exposure - Jianning Chang; Haibo Zhang; Jinsong Liang; Guangming Zhang; Yajie Zhang; Ru Zhang; Maoqing Wang; Su Shiung Lam; Shaoqing Guo; Panyue Zhang (Environmental Research, 2026)

Soil respiration and its temperature sensitivity on croplands in response to biotic and abiotic factors under straw and nitrogen fertilizer management - Ru Guo; Ruixuan Hao; Xiaoyi Yang; Rui Qian; Zijun Ma; Yunyun Yang; Peng Zhang; Zhikuan Jia; Yuncheng Liao; Xiaolong Ren; Xiaoli Chen (CATENA, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

Seasonal and day-night variations in light absorption properties of humic-like substances and effects of aqueous-phase photooxidation - Wei Yuan; Jing Duan; Ting Wang; Yi Liu; Jie Guo; Wenjuan Cao; Ru-Jin Huang (Atmospheric Research, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Potentials of food-derived peptides as novel antihypertensive agents and their acting mechanisms - Ru-Xue Guo; Liang Shen (Food Chemistry, 2025)

Hydrophobic surface modified calcium alginate fibers for preparing flame retardant and comfortable Janus fabrics - Yue Ma; Zihan Wu; Meijie Qu; Ru Chen; Jing Guo; Yuezhen Bin (Carbohydrate Polymers, 2025)

Pyrolysis behavior of local environmentally harmful Erigeron Canadensis L.: a kinetic model using thermogravimetric analysis and multi-prediction - Tianrui Han; Ke Xie; Xiaolei Ye; Lei Gao; Shenghui Guo; Haohang Ji; Juanjian Ru; Botao Gao; Li Yang (Biomass and Bioenergy, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Gut microbiome-targeted therapeutics for chronic kidney disease: comparative efficacy of probiotic and microbial preparations - Yi-Ke Li; Wen-Ru Li; Huan Ren; Chen-Lin Xiao; Zhen Guo; Jian-Quan Luo (Inflammopharmacology, 2025)

Identification of the Q-type ZFP gene family in Triticeaes and drought stress expression analysis in common wheat - Pengyan Guo; Changyan Cui; Baoquan Quan; Jiping Zhao; Jingna Ru; Yanzhen Wang; Zhiyuan Song; Aohui Lin; Shuwen He; Guanghao Wang (Genetica, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Schwertmannite maintains effective stabilization of arsenic in flooded paddy soil: Insights from a two-season rice experiment and underlying mechanisms - Ru Wang; Yang Song; Yinglin Guo; Nan Ge; Xiaomeng Wang; Lixiang Zhou; Guanyu Zheng (Journal of Hazardous Materials, 2025)

Multi-omics decodes exercise-induced geroprotection: betaine unlocks aging delay via TBK1 inhibition - Yang Li; Liang Guo; Ru Wang (Science China Life Sciences, 2025)

Modeling Dress-Out Traits Based on Morphological Traits in the Siberian Prawn, Exopalaemon modestus (Heller, 1862) - Liangjie Zhao; Zhiguo Hu; Congying Duan; Ru Zhang; Jiahui Liu; Xusheng Guo (Fishes, 2025)
Dress-out traits, such as abdominal meat weight and abdominal meat percentage, are difficult to improve through direct selection in aquatic species due to the lack of reliable measurement methods. To facilitate the prediction of these traits from morphological characteristics in live prawn, Exopalaemon modestus, a total of 518 individuals were collected in 2025 from Suyahu Reservoir in the upper Huaihe River, China. After excluding individuals with incomplete appendages and egg-bearing females, 301 prawns were randomly selected for model development, and the remaining 60 were used for validation. Based on integrated grey relational analysis and path analysis, body mass was identified as the most effective predictor of abdominal meat weight (p

Boosting brains: exercise enhances cognition and neurone density in a fish reared for release into nature - Yimeng Wang; Mengjia Tian; Haoyu Guo; Joacim Näslund; Yucheng Wang; Jiangfeng Ru; Yulu Qi; Kuo Tian (Animal Behaviour, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Hydrological variations dominate long-term ecological dynamics in a large alpine Lake Issyk-Kul, arid Central Asia: Evidence from sediment multi-biomarker analyses - Hongliang Zhang; Jinglu Wu; Ru Guo; Miao Jin; Long Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Porous Janus membrane for ultrasensitive detection and efficient degradation of sulfur mustard simulant - Meiyang Jin; Shuya Liu; Hailong Jiang; Xia Wang; Yongxian Guo; Yanjun Gong; Qiongzheng Hu; Ru-Song Zhao (Journal of Hazardous Materials, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

Fabrication of self-supported amorphous layered double hydroxides/bamboo biochar electrode for boosting its performance as symmetric supercapacitors - Zhuo Wang; Xiao Li; Qing Cai; Zhao-Yang Pan; Li Li; Yuan-Ru Guo; Qing-Jiang Pan (Chemical Engineering Journal, 2025)

The industrial biocide benzisothiazolinone impairs pathogen resistance in larval zebrafish by inducing microbiota dysbiosis - Meiping Guo; Yue Wang; Yang Yang; Lei Shao; Shuhui Wei; Liqiang Yang; Pengfei Cui; Shaoguo Ru; Xiaona Zhang (Aquatic Toxicology, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

The Mechanism of the Effect of FCC Slurry Oil Blending Ratio on the Colloidal Stability and Asphaltene Aggregation Behavior of Low-Sulfur Marine Fuel Oil - Aigang Li; Shengjun Guo; Jianwen Deng; Hong Chen; Jinxuan Wu; Ru Jiang; Jing Tan; Lihua Cheng; Libo Zhang; Qinzhen Fan (Journal of Marine Science and Engineering, 2025)
Addressing IMO 2020 compliance, this study investigates marine fuel oil production from hydrotreated residues, focusing on mitigating excessive total sediment potential (TSP) caused by over-hydrotreatment. This study systematically investigates the impact of blending ratios of Fluid Catalytic Cracking (FCC) slurry oil with Residue Desulfurization (RDS) heavy oil on TSP, colloidal stability, and asphaltene structure evolution. Techniques such as XRD, SEM, and XPS were employed to analyze the structural changes in asphaltenes during the TSP exceeding process. The results indicate that as the FCC slurry oil blending ratio increases, TSP in the blended oil initially rises and then decreases. The peak TSP value of 0.41% occurs at a 10% FCC slurry oil blending ratio, primarily due to high-saturation hydrocarbons in RDS heavy oil disrupting the colloidal stability of asphaltenes in FCC slurry oil. When the blending ratio reaches 25%, TSP significantly decreases to 0.09%, attributed to the solubilizing effect of high aromatic compounds in the FCC slurry oil on the asphaltenes. The ω(Asp)/ω(Res) ratio mirrors the TSP trend, and the colloidal solubilizing capacity of asphaltenes increases with the blending ratio. Asphaltenes in RDS heavy oil exhibit a spherical structure, whereas those in FCC slurry oil show a layered structure. The precipitated asphaltenes in the blends primarily result from the aggregation of asphaltenes in FCC slurry oil, with heteroatoms (N, S, O) mainly originating from RDS heavy oil asphaltenes. During the early stage of blending, TSP formation is dominated by FCC slurry oil asphaltenes, but increasing the aromatic content in the system can significantly reduce TSP. This work provides theoretical and technical support for optimizing marine fuel blending processes in petrochemical enterprises.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Efficient Microbial Production of Selenium Nanoparticles by Selenium-Tolerant Alcaligenes sp. HZ-9-3-3 - Omer Hassan Ali Hassan; Ya-Ru Wei; Zai-Ping Feng; Jia-Mei Pei; Jia-Nan Xu; Wen-Tao Du; Qiang-qiang Gou; Wen-Di Wang; Xue Zhao; Qin-Cui Shi; Xin-Guo Zhang (Current Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Different responses of phytoplankton taxa to water N and P inputs in a freshwater wetland: A mesocosm study - Wenjing Ma; Jiayin Feng; Jinhua Zhang; Hongpeng Wang; Yunpeng Guo; Yaru Lyu; Chao Wang; Zixuan Yang; Mengyu Yan; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Marine Pollution Bulletin, 2025)

Isolation and identification of triterpenoid saponins with antiproliferative and hemolytic activities from Camellia oleifera Abel seeds - Jian-Fa Zong; Xiao-Xiang Guo; Kang-Kang Zou; Chuan-Jian Cui; Zi-Hui Hu; Ru-Yan Hou (Phytochemistry, 2025)

Indoor and outdoor bioaerosol distributions and concentration profiles during different seasons and pollution events in Qingdao city - Ru Zhao; Liang Guo; Jianhua Qi; Taicheng An (Building and Environment, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Spatial distribution changes and habitat conservation of medicinal plant diversity in the Yinshan Mountains (China) under climate change - Zeyuan Zhao; Yaqiong Bi; Xinxin Wei; Yuan Chen; Ru Zhang; Jingxia Guo; Mingxu Zhang; Xiaobo Zhang; Minhui Li (Journal of Geographical Sciences, 2025)

Four saprobic species associated with Mahonia in Guizhou Province, China - Ya-Ru Sun; Kevin D. Hyde; Ning-Guo Liu; Fatimah O. Al-Otibi; Yong Wang; Ruvishika S. Jayawardena (Mycological Progress, 2025)

Fabrication, characterization, and application in 3D printing of high internal phase emulsion stabilized by alkaline thermal treated pea protein and pectin complex - Ru Zhao; Boxue Xia; Abbas Khan; Yanjiao Chang; Xin Guo; Yaxuan Liu; Xin Huang; Cuina Wang (Food Research International, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Holocene hydroclimatic changes inferred from a mountainous lake sedimentary record on the southeastern Tibetan Plateau - Jianchao Zhou; Jinglu Wu; Ru Guo; Ming Ji (International Journal of Earth Sciences, 2025)

How do different ant species mediate CH4 fluxes in slash-burn tropical forest soils? - Lingling Xie; Shaojun Wang; Mei Lu; Bo Xiao; Zhengjun Wang; Zhipeng Guo; Xiaofei Guo; Shuang Luo; Ru Li; Jiahui Xia; Shengqiu Yang; Mengjie Lan (Soil and Tillage Research, 2025)

Energy storage in Hf0.5Zr0.5O2(3):ZrO2(12)-based films with heterostructures formed at different deposition temperatures - Haiyan Chen; Chengfeng Jiang; Lei Liu; Ru Guo; Zhongna Yan; Chuanchang Li; Dou Zhang (Chemical Engineering Journal, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Quantitational life cycle assessment of Effluent-Energy-Carbon synergies and trade-offs in drinking water treatment plant upgrades - Yumeng Zhang; Zongqi Ding; Zewei Lin; Shoubin Chen; Shunjian Cheng; Kaiming Peng; Ru Guo; Xiangfeng Huang; Chen Cai; Jia Liu (Journal of Water Process Engineering, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

A 200-year record of polycyclic aromatic hydrocarbon (PAH) deposition in Lake Balkhash, arid Central Asia: PAH sources and inferred human history - Ru Guo; Jinglu Wu; Miao Jin; HongLiang Zhang; Long Ma (Journal of Paleolimnology, 2025)

Endophytes and soil microorganisms participate in the germination of Sinojackia xylocarpa Hu by degrading the pericarp - Zi-Hao Li; Xin-Yi Ma; Huan Yang; Run-Guo Zang; Jia-Ru Li (Acta Physiologiae Plantarum, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Pathways for supply security and carbon-neutral transition in the oil products industry: A comprehensive technology portfolio evaluation - Li Shang; Zheng Lyu; Nannan Sun; Guofei Shen; Qun Shen; Ru Guo; Wei Wei (Journal of Cleaner Production, 2025)

Structural characteristics of lotus seed starch-chlorogenic acid complexes during dynamic in vitro digestion and prebiotic activities - Xiaoying Wang; Ru Jia; Wenyu Chen; Baodong Zheng; Zebin Guo (Food Chemistry, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Dissimilatory nitrate reduction to ammonium driven by different electron donors: Mechanisms, recent advances, and future perspectives - Wan-Ru Wen; Tian-Chen Liu; Sheng-Qiang Fan; Xin Tan; Yang Lu; De-Feng Xing; Bing-Feng Liu; Nan-Qi Ren; Guo-Jun Xie (Chemical Engineering Journal, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Tetrachlorantraniliprole induces neurodevelopmental toxicity through oxidative stress-mediated apoptosis and dysregulation of Wnt signaling pathway - Ru Guo; Youjuan Wu; Tingting Yu; Chen Guo; Zijia Yin; Guannan Zhao; Meifeng Li; Huiling Mao; Chengyu Hu; Xiaowen Xu (Aquatic Toxicology, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Impact of lotus seed Starch-EGCG complex on gut microbiota: Structural changes and fermentation effects - Ru Jia; Lu Liu; Wenjing Chen; Wenyu Chen; Xiaoying Wang; Zebin Guo (Food Bioscience, 2025)

Effects of imidacloprid on Orius similis: assessing growth, development, and reproduction through age-stage two-sex life table analysis under contact and stomach toxicity treatments - Bo Zhang; Yi-Ru Li; Jin-Long Zhang; Guo-Hua Chen; Nian Yang; Ji-Huan Liu; Guo-Ting Yuan; Xiao-Ming Zhang (Journal of Pest Science, 2025)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Enhancing natural carbon sinks: Simulation of land use change under different carbon market scenarios by developing an ANN-ABM model - Ruimin Lin; Ru Guo; Yunyang Li; Guanghui Shao; Yuhao Zhang; Kaiming Peng; Xiangfeng Huang (Resources, Conservation and Recycling, 2024)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

Zebrafish FKBP5 facilitates apoptosis and SVCV propagation by suppressing NF-κB signaling pathway - Zijia Yin; Hongying Zhang; Kaiwen Zhao; Yulong Liu; Ru Guo; Pengxia Xu; Guannan Zhao; Menglei Hu; Chengyu Hu; Xiaowen Xu (Fish & Shellfish Immunology, 2024)

Evaluating the multi-seasonal impacts of urban blue-green space combination models on cooling and carbon-saving capacities - Fei Yang; Dongdong Yang; Ying Zhang; Ru Guo; Jiaying Li; Hongcheng Wang (Building and Environment, 2024)

Cell-permeable PI3 kinase competitive peptide inhibits KIT mutant mediated tumorigenesis of gastrointestinal stromal tumor (GIST) - Zongying Jiang; Yue Guo; Jun Shi; Shaoting Zhang; Liangying Zhang; Yapeng Wang; Guofu Li; Ru Bai; Hui Zhao; Jianmin Sun (Molecular Biology Reports, 2024)

Devosia lacusdianchii sp. nov., an attached bacterium inhibited by metabolites from its symbiotic Microcystis - Qing-Lin Deng; Yao Xiao; Ru Jia; Xin Xie; Le Wang; Xin Wang; Jian-Yuan Yang; Qi-Gen Guo; Bing-Huo Zhang (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Metabolic pathways altered by air pollutant exposure in association with coagulation function among the rural elderly - Haoyu Huang; Ru-Qing Liu; Yan Chen; Yuewei Liu; Guang-Hui Dong; Jian Hou; Shanshan Li; Yuming Guo; Chongjian Wang; Gongbo Chen (Journal of Hazardous Materials, 2024)

Technology-driven carbon-neutral pathway analysis for Urban Wastewater Treatment Plants - Haoran Wu; Chen Cai; Lian Yu; Zhenxing Shang; Yumeng Zhang; Xiaojing Ni; Ru Guo; Jia Liu; Kaiming Peng; Xiangfeng Huang; Limin Zhang; Zhaochang Huang; et al. (Journal of Cleaner Production, 2024)

Comparative study on dynamic in vitro digestion characteristics of lotus seed starch-EGCG complex prepared by different processing methods - Wenjing Chen; Ru Jia; Lu Liu; Wanyi Lin; Zebin Guo (Food Chemistry, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Ingenane-type diterpenoids inhibit non-small cell lung cancer cells by regulating SRC/PI3K/Akt pathway - Xin-Ye Wang; Yu-Jue Wang; Zi-Lin Hou; Bo-Wen Guo; Ru-Qi Wang; Qingbo Liu; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2024)

One new 12, 8-guaianolide sesquiterpene lactone with antihyperglycemic activity from the roots of Cichorium intybus - Xiu-hua Meng; Yin-an Pan; Han Lv; Xiao-qin Ding; De-quan Yin; Ya-nan Gai; Guan-ting Niu; Bing-ru Ren; Xiao-guo Qian; Jian Chen (Natural Product Research, 2024)

Unraveling the characteristics of microplastics in agricultural soils upon long-term organic fertilizer application: A comprehensive study using diversity indices - Sen Guo; Guangmin Xiao; Yanhua Chen; Jiajia Zhang; Baogui Zhang; Shuhua Ru; Meng Zhao (Chemosphere, 2024)

Long-term exposure to prometryn damages the visual system and changes color preference of female zebrafish (Danio rerio) - Shuhui Wei; Yixin Yang; Yao Zong; Yang Yang; Meiping Guo; Zhenzhong Zhang; Rui Zhang; Shaoguo Ru; Xiaona Zhang (Chemosphere, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Upgrading the industrial structure for optimizing water-energy-carbon nexus in regional trade network - Benshuo Zhu; Ru Guo; Yun-en Tang; Kaiming Peng; Xiangfeng Huang (Journal of Cleaner Production, 2024)

Non-covalent interactions-advanced selective trapping of flexible nitrilotriacetamide towards radioactive pertechnetate - Ding Xie; Juan Wang; Yu-Chang Hou; Yuan-Ru Guo; Songdong Ding; Qing-Jiang Pan (Chemical Engineering Journal, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Alginate/silk fibroin/Zn2+ composite microspheres for site-specific delivery for enhanced ulcerative colitis therapy - Yaoyao Du; Yuting Jiang; Yijie Song; Jie Chen; Yueqian Wu; Ru Guo; Yihao He; Lan Shen; Bing Wang; Shaogang Huang; Yongzhuo Huang (Chemical Engineering Journal, 2024)

Astrocyte Activation in the ACC Contributes to Comorbid Anxiety in Chronic Inflammatory Pain and Involves in The Excitation-Inhibition Imbalance - Naixuan Wei; Zi Guo; Mengting Qiu; Ru Ye; Xiaomei Shao; Yi Liang; Boyi Liu; Jianqiao Fang; Junfan Fang; Junying Du (Molecular Neurobiology, 2024)

Spatio-temporal evolution and driving mechanism of metal value flow networks: A global value chain perspective - Yiwen Deng; Yaoqi Guo; Hongwei Zhang; Ru Zheng (Journal of Cleaner Production, 2024)

Effect of heating treatment on processing characteristics of rice dough - Wan-ru Liu; Chun-min Ma; Yang Yang; Bing Wang; Xiao-fei Liu; Yan Wang; Xin Bian; Xiao-xue Guo; Guang Zhang; Na Zhang (Innovative Food Science & Emerging Technologies, 2024)

MGAtt-LSTM: A multi-scale spatial correlation prediction model of PM2.5 concentration based on multi-graph attention - Bo Zhang; Weihong Chen; Mao-Zhen Li; Xiaoyang Guo; Zhonghua Zheng; Ru Yang (Environmental Modelling & Software, 2024)

Long-term dynamics of organic matter inputs in sediments of Lake Balkhash, arid Central Asia: Coupled climate and anthropogenic influences - Hongliang Zhang; Jinglu Wu; Ru Guo; Long Ma (CATENA, 2024)

Distance-decay equations of antibiotic resistance genes across freshwater reservoirs - Zhao-Feng Guo; Kiranmoy Das; Wiebke J. Boeing; Yao-Yang Xu; Edoardo Borgomeo; Dong Zhang; Si-Cheng Ao; Xiao-Ru Yang (Water Research, 2024)

Spatial equity of urban parks from the perspective of recreational opportunities and recreational environment quality: A case study in Singapore - Ru Guo; Jessica Ann Diehl; Ran Zhang; Hongcheng Wang (Landscape and Urban Planning, 2024)

Electronic-rich large conjugated molecules dispersing through ionic liquid solution process for fluorescent detection of iodine gas - Yue-Ru Zhou; Shuang-Long Wang; Lei Zhang; Jie Fu; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2024)

Screening of Strain from Reconstituted Sheet Tobacco Making High-Yield Enzyme and Aroma - Chun-Xue Yang; Deng Zhang; Hui Ma; Xiao-Meng Guo; Na Yan; Xue-Ting Deng; Xiang-Ru Liao; Zheng-Bing Guan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Effects of exercise training on the external morphology, growth performance, swimming ability, body composition and metabolism of juvenile black seabream Acanthopagrus schlegelii - Haoyu Guo; Jinbo Zhai; Mengjia Tian; Joacim Näslund; Jiangfeng Ru; Yingying Ou; Yulu Qi; Qingsong Hu; Kai Liu; Xiumei Zhang (Aquaculture, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

History of organic pollution in montane lake Issyk-Kul, Kyrgyzstan, Central Asia, inferred from a sediment core - Ru Guo; Jinglu Wu; HongLiang Zhang; Qianyu Li (Environmental Research, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Potential use of maize–peanut intercropping to adapt to drought and nitrogen–shortage impacts - Fei Han; Shuqing Guo; Muhammad Asad Naseer; Ru Guo; Tie Cai; Peng Zhang; Zhikuan Jia; Dong Yang; XiaoLi Chen; Xiaolong Ren (Plant and Soil, 2024)

Cadmium Treatment Affected the Growth and Physiology of Larix Olgensis Seedlings, the Chemical Properties of Haplic Cambisols and Toxicity Threshold Determination - Haixia Wang; Kunshu Yao; Jiaxin Ru; Jiagui Guo; Ding Liu; Yunlong Liu; LingYun Bai; Jixiang Lin; Chengbo Gu; Jinfeng Song (Journal of Soil Science and Plant Nutrition, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Effect of the CYBA C242T Polymorphism on Preeclampsia Pathogenesis in the Chinese Population - Ru Zhang; Shuhui Liu; Ping Tan; Zihan Guo; Huabin Hou; Shiguo Liu; Hui Li; Xibing Wang (Biochemical Genetics, 2024)

Application of a water-energy-carbon coupling index to evaluate the long-term operational stability of the anaerobic-anoxic-oxic-membrane bioreactor (A2/O-MBR) process under the influence of rainstorms - Lian Yu; Kaiming Peng; Yizhen Huang; Feng Chen; Shoubin Chen; Yulong Xia; Xiangfeng Huang; Xiaojing Ni; Ru Guo; Chen Cai; Jia Liu (Water Research, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Nighttime warming and nitrogen addition effects on the microclimate of a freshwater wetland dominated by Phragmites australis - Yunpeng Guo; Jian Song; Jiayin Feng; Hongpeng Wang; Jinhua Zhang; Jingyi Ru; Xiaopan Wang; Xu Han; Huixia Ma; Yaru Lyu; Wenjing Ma; Chao Wang; et al. (Science of The Total Environment, 2024)

Direct and indirect monitoring methods for nitrous oxide emissions in full-scale wastewater treatment plants: A critical review - Zhenxin Shang; Chen Cai; Yanli Guo; Xiangfeng Huang; Kaiming Peng; Ru Guo; Zhongqing Wei; Chenyuan Wu; Shunjian Cheng; Youxiang Liao; Chih-Yu Hung; Jia Liu (Journal of Environmental Management, 2024)

A novel ionic-liquid-mediated covalent organic framework as a strong electrophile for high-performance iodine removal - Jie Fu; Jia-Ying Liu; Yue-Ru Zhou; Lei Zhang; Shuang-Long Wang; Song Qin; Maohong Fan; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Redirecting surface reconstruction of CoP-Cu heterojunction to promote ammonia synthesis at industrial-level current density - Li Gan; Xiaoxue Zhang; Lei Guo; Muhammad Ajmal; Ru Jia; Xiaolei Guo; Chengxiang Shi; Lun Pan; Faryal Idrees; Xiangwen Zhang; Zhen-Feng Huang; Guidong Yang; et al. (Chemical Engineering Journal, 2024)

Exercise-induced microbial changes in preventing type 2 diabetes - Ting Yao; Hui Wang; Kaiqing Lin; Ruwen Wang; Shanshan Guo; Peijie Chen; Hao Wu; Tiemin Liu; Ru Wang (Science China Life Sciences, 2024)

Carbon emissions of urban rail transit in Chinese cities: A comprehensive analysis - Jing Pu; Chen Cai; Ru Guo; Jiangchuan Su; Ruimin Lin; Jia Liu; Kaiming Peng; Chaoguang Huang; Xiangfeng Huang (Science of The Total Environment, 2024)

Proteomics revealed composition- and size-related regulators for hepatic impairments induced by silica nanoparticles - Xinying Zhao; Ru Ma; Alimire Abulikemu; Yi Qi; Xiaoying Liu; Ji Wang; Kun Xu; Caixia Guo; Yanbo Li (Science of The Total Environment, 2024)

On the origin of selectivity in extracting and separating lanthanide ions by alkyl-nitrilotriacetamide - Yu-Chang Hou; Juan Wang; Yuan-Ru Guo; Song-Dong Ding; Qing-Jiang Pan (Chemical Engineering Journal, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Risk factors for short-term prognosis of end-stage liver disease complicated by invasive pulmonary aspergillosis - Weiyan Yu; Ying Xiao; Yue Luo; Yangyang Hu; Ru Ji; Wei Wang; Zhinian Wu; Zeqiang Qi; Tingyu Guo; Yadong Wang; Caiyan Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Lower-bound shakedown solutions for transportation infrastructures subjected to moving harmonic loads: A focus on saturated subgrade support - Yuanxiang Lin; Jun-Jie Zheng; Hao Fang; Ru-Yi Hou; Yifan Guo (Transportation Geotechnics, 2024)

Responses of sediment n-alkanes to climate factors and anthropogenic disturbances from three lakes with different elevations, arid Central Asia - Hongliang Zhang; Jinglu Wu; Qianyu Li; Ru Guo (Science of The Total Environment, 2024)

Enhancing phenology modeling through the integration of artificial light at night effects - Haoming Xia; Longxin Qiao; Yan Guo; Xutong Ru; Yaochen Qin; Yuyu Zhou; Chaoyang Wu (Remote Sensing of Environment, 2024)

6PPD-quinone exposure induces neuronal mitochondrial dysfunction to exacerbate Lewy neurites formation induced by α-synuclein preformed fibrils seeding - Jiacheng Fang; Xiaoxiao Wang; Guodong Cao; Fuyue Wang; Yi Ru; Bolun Wang; Yanhao Zhang; Doudou Zhang; Jie Yan; Ji Xu; Jing Ji; Fenfen Ji; et al. (Journal of Hazardous Materials, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Tea polyphenols alleviate TBBPA-induced inflammation, ferroptosis and apoptosis via TLR4/NF-κB pathway in carp gills - Ran Xu; Fu-xin Han; Hong-ru Wang; Jing-jing Wang; Zhao-long Cai; Meng-yao Guo (Fish & Shellfish Immunology, 2024)

Optimizing maize productivity: A sustainable approach integrating straw derivatives and film mulching in rainfed agriculture - Rui Qian; Zijun Ma; Yunyun Yang; Ru Guo; Fei Han; Jinjin Wang; Xiaoling Wang; Baoping Sun; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Field Crops Research, 2024)

Integrated straw-derived biochar utilization to increase net ecosystem carbon budget and economic benefit and reduce the environmental footprint - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2024)

Sedimentary records of polycyclic aromatic hydrocarbons and organochlorine pesticides to reconstruct anthropogenic activities in Lake Issyk-Kul region (Kyrgyzstan), and their effects on the lake environment - Qianyu Li; Guo Ru; Jinglu Wu; Miao Jin (Anthropocene, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Can straw recycling achieve sustainable agriculture at the smallholder level? A case in a semi-arid region - Rui Qian; Ru Guo; Qingxuan Yang; Muhammad Asad Naseer; Baoping Sun; Longlong Wang; Jian Zhang; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Journal of Cleaner Production, 2024)

Maize/peanut rotation intercropping improves ecosystem carbon budget and economic benefits in the dry farming regions of China - Fei Han; Talha Javed; Sadam Hussain; Shuqing Guo; Ru Guo; Lihua Yang; Xiantong Liu; Tie Cai; Peng Zhang; Zhikuan Jia; Anis Ali Shah; Xiaoli Chen; et al. (Journal of Environmental Management, 2024)

Influence of labor migration on rural household food waste in China: Application of propensity score matching (PSM) - Guohui Shen; Xin Ru; Kunzhen Wang; Ziqi Li; Mingxue Yu; Lu Chen; Juan Han; Yanzhi Guo (Journal of Environmental Management, 2024)

Impact of straw and its derivatives on lodging resistance and yield of maize (Zea mays L.) under rainfed areas - Rui Qian; Ru Guo; Guangxu Guo; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (European Journal of Agronomy, 2024)

Design, synthesis and insecticidal activity of benzenesulfonamide derivatives containing various alkynyl, alkenyl and cyclopropyl groups in para position - Jian-Jun Zhu; Tao Guo; Hong-Xiang Liu; Xin-Ru Tan; Zi-Wei Zhang; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Bifidobacteria in disease: from head to toe - Weiliang Zhang; Qiang Jia; Mingming Han; Xin Zhang; Limin Guo; Shichao Sun; Wenhui Yin; Cunxiang Bo; Ru Han; Linlin Sai (Folia Microbiologica, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Tree ring oxygen isotope in Asia - Chenxi Xu; Ru Huang; Wenling An; Qingyu Zhao; Yaru Zhao; Junbo Ren; Yucheng Liu; Zhengtang Guo (Global and Planetary Change, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

High-strength ionic hydrogel constructed by metal-free physical crosslinking strategy for enhanced uranium extraction from seawater - Yuan-Hao Wang; Yu-Qin Xiang; Qian Huang; Xiao-Lan Yang; Shuang-Long Wang; Yue-Ru Zhou; Song Qin; Ling-Qiong Gou; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Sympatric munias in tropical areas segregate spatially through different nest site selections to achieve coexistence - Chen-Wei Guo; Li-Li Li; Chen-Yang Liu; Ru-Chuan He; Rui-Chang Quan (Acta Oecologica, 2024)

A Dual Functional Fluorescent Probe Based on Phenothiazine for Detecting Hg2+ and ClO− and its Applications - Cheng-lu Zhang; Chang Liu; Shi-ru Nie; Yang Zhang; Jing-hao Guo; Xiang-ling Li; Cui Liu (Journal of Fluorescence, 2023)

Corrigendum to “Silica nanoparticles promote oxLDL-induced macrophage lipid accumulation and apoptosis via endoplasmic reticulum stress signaling” [Sci. Total Environ., 631-632 (2018): 570-579] - Caixia Guo; Ru Ma; Xiaoying Liu; Tian Chen; Yang Li; Yang Yu; Junchao Duan; Xianqing Zhou; Yanbo Li; Zhiwei Sun (Science of The Total Environment, 2023)

Plastic pollution from takeaway food industry in China - Qian-Qian Zhang; Min-Yi Lan; Hui-Ru Li; Shu-Qing Qiu; Zhao Guo; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2023)

Insights into greenhouse gas emissions from a wastewater treatment plant in vulnerable water areas of China - Jiemiao Ma; Xiaojing Ni; Chen Cai; Yuewu Da; Kan Hu; Ru Guo; Jia Liu; Kaiming Peng; Erwu Liu; Xiangfeng Huang (Science of The Total Environment, 2023)

The protective immunity induced by Trichinella spiralis galectin against larval challenge and the potential of galactomannan as a novel adjuvant - Ru Zhang; Xin Zhuo Zhang; Xin Guo; Lu Lu Han; Bo Ning Wang; Xi Zhang; Ruo Dan Liu; Jing Cui; Zhong Quan Wang (Research in Veterinary Science, 2023)

Polyethylene microplastics cause apoptosis via the MiR-132/CAPN axis and inflammation in carp ovarian - Meng-ran Zhu; Hong-ru Wang; Fu-xin Han; Zhao-long Cai; Jing-jing Wang; Meng-yao Guo (Aquatic Toxicology, 2023)

Influence of Nitrogen Application on Soil Chemical Properties, Nutrient Acquisition, and Enzymatic Activities in Rainfed Wheat/Maize Strip Intercropping - Sadam Hussain; Muhammad Asad Naseer; Fei Han; Ru Guo; Muhammad Saqib; Muhammad Farooq; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Deep insights into the population shift of n-DAMO and Anammox in granular sludge: From sidestream to mainstream - Sheng-Qiang Fan; Wan-Ru Wen; Guo-Jun Xie; Yang Lu; Bing-Feng Liu; De-Feng Xing; Jun Ma; Nan-Qi Ren (Water Research, 2023)

Harnessing microbial phylum-specific molecular markers for assessment of environmental estrogen degradation - Tsun-Hsien Hsiao; Po-Hao Chen; Po-Hsiang Wang; Guo-Jie Brandon-Mong; Chen-Wei Li; Masae Horinouchi; Toshiaki Hayashi; Wael Ismail; Menghsiao Meng; Yi-Lung Chen; Yin-Ru Chiang (Science of The Total Environment, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Creep properties and energy evolution characteristics of weakly cemented rock under step loading - Shanchao Hu; Chenxi Zhang; Wenkai Ru; Jinming Han; Shihao Guo; Xuedong Zhou; Lei Yang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Burden of cardiovascular disease attributable to long-term exposure to ambient PM2.5 concentration and the cost–benefit analysis for the optimal control level - Chu-Chih Chen; Yin-Ru Wang; Jhi-Shin Liu; Hsing-Yi Chang; Yue Leon Guo; Pau-Chung Chen (Science of The Total Environment, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Enhancing fiber–matrix interface permeability resistance of natural fiber-reinforced, bio-cemented sand by CaCO 3 seed pretreatment - Liang Guo; Qichen Dai; Xingzhu Lin; Yuhong Jiang; Baoquan Wang; Xiaohua Pan; Yiqi Peng; Guoqiang Zhao; Yi Ru; Liye Zhou (Geomechanics for Energy and the Environment, 2023)

Toxic effects of perfluorocaproic acid (PFHxA) on crucian carp (Carassius auratus) and the response of the intestinal microbial community - Xue Jiao; Zheng yao Guo; Bing li Liu; Long tao Wang; Zhi nan Yang; Yuan ru Yang; Ai-dong Qian; Yue-hong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Estimation of in-season nitrogen requirement for drip-irrigated spring maize without or with straw incorporation using critical nitrogen dilution curve - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Plant and Soil, 2023)

Pinellia ternata PtZS1 contributes to abiotic stress responses via the antioxidant pathway - Ru Li; Weiyue Guo; Pan Li; Kang Lei; Lusha Ji (Journal of Plant Biochemistry and Biotechnology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A Co2N/CoP p-n junction with modulated interfacial charge and rich nitrogen vacancy for High-Efficiency water splitting - Chunfang Guo; Hui Xue; Jing Sun; Niankun Guo; Tianshan Song; Jiawen Sun; Yi-Ru Hao; Qin Wang (Chemical Engineering Journal, 2023)

Contributions of abundant and rare bacteria to soil multifunctionality depend on aridity and elevation - Peng He; Ning Ling; Xiao-Tao Lü; Hai-Yang Zhang; Chao Wang; Ru-Zhen Wang; Cun-Zheng Wei; Jing Yao; Xiao-Bo Wang; Xing-Guo Han; Zhibiao Nan (Applied Soil Ecology, 2023)

Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPARγ/NF-κB signaling - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhu Yang; Zongwei Cai; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Effects of fungal agents and biochar on odor emissions and microbial community dynamics during in-situ treatment of food waste - Shu-Ping Zou; Ru-Sheng Liu; Yu Luo; Chun-Tao Bo; Su-Qin Tang; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Study on Mechanical Property of Coal-Rock Combination Under Different Unloading Confining Pressure Rate - Shanchao Hu; Xuedong Zhou; Wenkai Ru; Jinming Han; Shihao Guo; Chenxi Zhang; Lei Yang (Geotechnical and Geological Engineering, 2023)

Evolutionary origin and establishment of a dioecious diploid‐tetraploid complex - Li He; Fei‐Yi Guo; Xin‐Jie Cai; Hong‐Pu Chen; Chun‐Lan Lian; Yuan Wang; Ce Shang; Yue Zhang; Natascha Dorothea Wagner; Zhi‐Xiang Zhang; Elvira Hörandl; Xiao‐Ru Wang (Molecular Ecology, 2023)
Polyploids recurrently emerge in angiosperms, but most polyploids are likely to go extinct before establishment due to minority cytotype exclusion, which may be specifically a constraint for dioecious plants. Here we test the hypothesis that a stable sex‐determination system and spatial/ecological isolation facilitate the establishment of dioecious polyploids. We determined the ploidy levels of 351 individuals from 28 populations of the dioecious species Salix polyclona , and resequenced 190 individuals of S . polyclona and related taxa for genomic diversity analyses. The ploidy survey revealed a frequency 52% of tetraploids in S . polyclona , and genomic k ‐mer spectra analyses suggested an autopolyploid origin for them. Comparisons of diploid male and female genomes identified a female heterogametic sex‐determining factor on chromosome 15, which probably also acts in the dioecious tetraploids. Phylogenetic analyses revealed two diploid clades and a separate clade/grade of tetraploids with a distinct geographic distribution confined to western and central China, where complex mountain systems create higher levels of environmental heterogeneity. Fossil‐calibrated phylogenies showed that the polyploids emerged during 7.6–2.3 million years ago, and population demographic histories largely matched the geological and climatic history of the region. Our results suggest that inheritance of the sex‐determining system from the diploid progenitor as intrinsic factor and spatial isolation as extrinsic factor may have facilitated the preservation and establishment of polyploid dioecious populations.

The coupling of graphene, graphitic carbon nitride and cellulose to fabricate zinc oxide-based sensors and their enhanced activity towards air pollutant nitrogen dioxide - Hua-Min Xiao; Yu-Chang Hou; Yuan-Ru Guo; Qing-Jiang Pan (Chemosphere, 2023)

Tantalum trade structural dependencies are what we need: A perspective on the industrial chain - Yaoqi Guo; Ru Zheng; Hongwei Zhang (Resources Policy, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Characteristics of greenhouse gases emission from wastewater treatment plants operation in China (2009–2016): A case study using operational data integrated method (ODIM) - Jiarui Xi; Hui Gong; Ru Guo; Ling Chen; Xiaohu Dai (Journal of Cleaner Production, 2023)

Long-term straw incorporation regulates greenhouse gas emissions from biodegradable film farmland, improves ecosystem carbon budget and sustainable maize productivity - Rui Qian; Ru Guo; Muhammad Asad Naseer; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2023)

Remediating flooding paddy soils with schwertmannite greatly reduced arsenic accumulation in rice (Oryza sativa L.) but did not decrease the utilization efficiency of P fertilizer - Ru Wang; Yinglin Guo; Yang Song; Yuting Guo; Xiaomeng Wang; Quan Yuan; Zengping Ning; Chengshuai Liu; Lixiang Zhou; Guanyu Zheng (Environmental Pollution, 2023)

Flexible, biocompatible, degradable silk fibroin based display - Zijie Xu; Zhi He; Jiani Huang; Wu Qiu; Leo N.Y. Cao; Aniruddha Patil; Bo-Ru Yang; Xiang Yang Liu; Wenxi Guo (Chemical Engineering Journal, 2023)

The status of the global food waste mitigation policies: experience and inspiration for China - Guohui Shen; Ziqi Li; Tiannuo Hong; Xin Ru; Kunzhen Wang; Yanting Gu; Juan Han; Yanzhi Guo (Environment, Development and Sustainability, 2023)
Food waste has become a significant challenge faced by the community with a shared future for mankind, and it has also caused a considerable impact on China's food security. Scholars across disciplines, international organizations, and especially policymakers are increasingly interested in food waste. Policies are seen as a powerful factor in reducing food waste, but current research on related policies is more scattered. This paper summarizes and analyzes the experiences of food waste policy development and implementation by systematically reviewing the studies on food waste reduction policies. The results of this paper's analysis show that current global food waste policies are focused at the national strategic level, with approaches such as legislation, food donation, waste recycling, awareness and education, and data collection. At the same time, we find that the current experience of developed countries in policy formulation and implementation is beneficial for policy formulation in developing countries. And taking China as an example, we believe that developing countries can improve food waste policies in the future by improving legislation, guiding the development of food banks, promoting social governance, and strengthening scientific research projects. These policies will all contribute strongly to global environmental friendliness. In addition, we discuss some of the factors that influence the development of food waste policies and argue that in the future, more consideration needs to be given to the effects of policy implementation and that case studies should focus more on developing countries. This will contribute to the global sustainable development process.

Pharmacokinetic profile and sub-chronic toxicity of coenzyme Q10 loaded whey protein nanoparticles - Cuina Wang; Ru Zhao; Keyi He; Siyu Zhang; Alyssa H. Kemp; Mingruo Guo (Food Bioscience, 2023)

Does increasing the organic fertilizer application rate always boost the antibiotic resistance level in agricultural soils? - Yajie Guo; Tianlei Qiu; Min Gao; Shuhua Ru; Haoze Gao; Xuming Wang (Environmental Pollution, 2023)

Application of microbial-induced carbonate precipitation (MICP) techniques to remove heavy metal in the natural environment: A critical review - Amit Kumar; He-Wei Song; Saurabh Mishra; Wei Zhang; Yu-Ling Zhang; Qian-Ru Zhang; Zhi-Guo Yu (Chemosphere, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Direct emissions of particulate glyoxal and methylglyoxal from biomass burning and coal combustion - Ting Wang; Ru-Jin Huang; Lu Yang; Wenting Dai; Haiyan Ni; Yuquan Gong; Jie Guo; Haobin Zhong; Chunshui Lin; Wei Xu (Science of The Total Environment, 2023)

Managing straw and nitrogen fertilizer based on nitrate threshold for balancing nitrogen requirement of maize and nitrate residue - Ru Guo; Rui Qian; Fei Han; Abdul Khaliq; Sadam Hussain; Ling Yang; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Journal of Environmental Management, 2023)

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

Rotation of planting strips and reduction in nitrogen fertilizer application can reduce nitrogen loss and optimize its balance in maize–peanut intercropping - Fei Han; Ru Guo; Sadam Hussain; Shuqing Guo; Tie Cai; Peng Zhang; Zhikuan Jia; Muhammad Asad Naseer; Muhammad Saqib; Xiaoli Chen; Xiaolong Ren (European Journal of Agronomy, 2023)

Treatment of heavy metal ions-polluted water into drinkable water: Capture and recovery of Pb2+ by cellulose@CaCO3 bio-composite filter via spatial confinement effect - He-Xiang Zhao; Yan Wang; Jun-Jie Yang; Ji-Guo Zhang; Yuan-Ru Guo; Shujun Li; Qing-Jiang Pan (Chemical Engineering Journal, 2023)

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Proteomic profiling reveals dysregulated mitochondrial complex subunits responsible for myocardial toxicity induced by SiNPs - Xinying Zhao; Hailin Xu; Yan Li; Ru Ma; Yi Qi; Min Zhang; Caixia Guo; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Water–energy–carbon synergies and trade-offs: A daily nexus analysis for wastewater treatment plants - Xiaojing Ni; Xiangfeng Huang; Ru Guo; Jinhui Wang; Kaiming Peng; Wei Zhang; Yuyu Zhu; Weilan Yang; Liya Wang; Chen Cai; Jia Liu; Erwu Liu (Resources, Conservation and Recycling, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Antimicrobial peptide hepcidin contributes to restoration of the intestinal flora after Aeromonas hydrophila infection in Acrossocheilus fasciatus - Qun-Yin Zhu; Ru-Yi Chen; Jing Yu; Guo-Hua Ding; Rachel Wan Xin Seah; Jie Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Preparation and application of recyclable polymer aerogels from styrene-maleic anhydride alternating copolymers - Yuan Yao; Xiaohong Zhang; Zhaoyan Guo; Wenlu Liu; Chenxi Hu; Yue Ru; Liangdong Zhang; Chao Jiang; Jinliang Qiao (Chemical Engineering Journal, 2023)

Citric acid-based deep eutectic solvent (CA-DES) as a new soil detergent for the removal of cadmium from coking sites - Jie Qian; Ying-hua Li; Fei Su; Ji-guo Wu; Jia-ru Sun; Tian-ci Huang (Environmental Science and Pollution Research, 2023)

Interactive Effects of Maize Straw-Derived Biochar and N Fertilization on Soil Bulk Density and Porosity, Maize Productivity and Nitrogen Use Efficiency in Arid Areas - Ru Guo; Rui Qian; Ling Yang; Abdul Khaliq; Fei Han; Sadam Hussain; Peng Zhang; Tie Cai; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

A fly GWAS for purine metabolites identifies human FAM214 homolog medusa, which acts in a conserved manner to enhance hyperuricemia-driven pathologies by modulating purine metabolism and the inflammatory response - Tyler A. U. Hilsabeck; Ru Liu-Bryan; Tracy Guo; Kenneth A. Wilson; Neelanjan Bose; Daniel Raftery; Jennifer N. Beck; Sven Lang; Kelly Jin; Christopher S. Nelson; Tal Oron; Marshall Stoller; et al. (GeroScience, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Phenomenon of the sediment deposition in a hydraulic jump region of open channels - Wei-lin Xu; Guo-guang Wang; Shi-hao Fu; Wang-ru Wei (Journal of Mountain Science, 2022)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Increase in rosmarinic acid accumulation and transcriptional responses of synthetic genes in hairy root cultures of Prunella vulgaris induced by methyl jasmonate - Mei Ru; Yonghua Li; Min Guo; Liuyan Chen; Yong Tan; Liang Peng; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Haloterrigena gelatinilytica sp. nov., a new extremely halophilic archaeon isolated from salt-lake - Bing-Bing Liu; Nimaichand Salam; Manik Prabhu Narsing Rao; Shuang Cheng; Yuan-Guo Xie; Lai-You Wang; Yuan-ru Zhang; Xin-Yuan Yu; Shu-xian Guo; Wen-Jun Li (Archives of Microbiology, 2022)

Infectivity and antigenicity of pseudoviruses with high-frequency mutations of SARS-CoV-2 identified in Portugal - Hai-xin Wang; Li Zhang; Zi-teng Liang; Jian-hui Nie; Jia-jing Wu; Qian-qian Li; Ru-xia Ding; Yue Zhang; Guo-qing Chen; You-chun Wang; Hui-guo Wang; Wei-jin Huang (Archives of Virology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a major impact on global human health. During the spread of SARS-CoV-2, weakened host immunity and the use of vaccines with low efficacy may result in the development of more-virulent strains or strains with resistance to existing vaccines and antibodies. The prevalence of SARS-CoV-2 mutant strains differs between regions, and this variation may have an impact on the effectiveness of vaccines. In this study, an epidemiological investigation of SARS-CoV-2 in Portugal was performed, and the VSV-ΔG-G* pseudovirus system was used to construct 12 spike protein epidemic mutants, D614G, A222V+D614G, B.1.1.7, S477N+D614G, P1162R+D614G+A222V, D839Y+D614G, L176F+D614G, B.1.1.7+L216F, B.1.1.7+M740V, B.1.258, B.1.258+L1063F, and B.1.258+N751Y. The mutant pseudoviruses were used to infect four susceptible cell lines (Huh7, hACE2-293T-293T, Vero, and LLC-MK2) and 14 cell lines overexpressing ACE2 from different species. Mutant strains did not show increased infectivity or cross-species transmission. Neutralization activity against these pseudoviruses was evaluated using mouse serum and 11 monoclonal antibodies. The neutralizing activity of immunized mouse serum was not significantly reduced with the mutant strains, but the mutant strains from Portugal could evade nine of the 11 monoclonal antibodies tested. Neutralization resistance was mainly caused by the mutations S477N, N439K, and N501Y in the spike-receptor binding domain. These findings emphasize the importance of SARS-CoV-2 mutation tracking in different regions for epidemic prevention and control.

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

A phenological object-based approach for rice crop classification using time-series Sentinel-1 Synthetic Aperture Radar (SAR) data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Piero Toscano; Youg-Sing Cheng; Hong-Yuh Guo; Chien-Hui Syu (International Journal of Remote Sensing, 2021)

Brominated and phosphate flame retardants from interior and surface dust of personal computers: insights into sources for human dermal exposure - Lehuan Yu; Shuling Ru; Xiaobo Zheng; Shejun Chen; Huiying Guo; Guijuan Gao; Yuan Zeng; Yijie Tang; Bixian Mai (Environmental Science and Pollution Research, 2021)

Decreased KLHL3 expression is involved in the activation of WNK-OSR1/SPAK-NCC cascade in type 1 diabetic mice - Qin Guo; Ya Zhang; Geng-Ru Jiang; Chong Zhang (Pflügers Archiv - European Journal of Physiology, 2021)

Comparison of Plasma Concentrations of Mercury, Cadmium, and Arsenic among Women in 2005 and 2012 in a Historically Contaminated Area in China - Lei Jin; Jing-ru Yu; Le Zhang; Ai-guo Ren (Biological Trace Element Research, 2020)

Machine learning approaches for rice crop yield predictions using time-series satellite data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Horng-Yuh Guo; Youg-Sing Cheng; Shu-Ling Chen; Huan-Sheng Lin; Shih-Hsiang Chen (International Journal of Remote Sensing, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Pasture degradation impact on soil carbon and nitrogen fractions of alpine meadow in a Tibetan permafrost region - Zi-Qiang Yuan; Qing-Bai Wu; Xin Song; Xiao-Jin Jiang; Si-Ru Gao; Qing-Feng Wang; Guo-Yu Li (Journal of Soils and Sediments, 2020)

Effects of small nucleolar RNA SNORD44 on the proliferation, apoptosis and invasion of glioma cells - Xian-Ru Xia; Wen-Cui Li; Zong-Tao Yu; Jie Li; Chun-Yan Peng; Li Jin; Guo-Lin Yuan (Histochemistry and Cell Biology, 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

Use of discrete choice experiments to facilitate design of effective environmentally friendly agricultural policies - Na-na Wang; Liang-guo Luo; Ya-ru Pan; Xue-mei Ni (Environment, Development and Sustainability, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

CBR-based integration of a hydrodynamic and water quality model and GIS—a case study of Chaohu City - Zhenliang Liao; Can Zhou; Wenchong Tian; Tiantian Hu; Ru Guo (Environmental Science and Pollution Research, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Hypoxia and nutrient dynamics affected by marine aquaculture in a monsoon-regulated tropical coastal lagoon - Jing Zhang; ZhuoYi Zhu; Wen Yuan Mo; Su Mei Liu; Dao Ru Wang; Guo Sen Zhang (Environmental Monitoring and Assessment, 2018)

Physiological Concentration of Prostaglandin E2 Exerts Anti-inflammatory Effects by Inhibiting Microglial Production of Superoxide Through a Novel Pathway - Shih-Heng Chen; Yueh-Feng Sung; Esteban A. Oyarzabal; Yu-Mei Tan; Jeremy Leonard; Mingri Guo; Shuo Li; Qingshan Wang; Chun-Hsien Chu; Shiou-Lan Chen; Ru-Band Lu; Jau-Shyong Hong (Molecular Neurobiology, 2018)

Cadmium phytoextraction potential of king grass (Pennisetum sinese Roxb.) and responses of rhizosphere bacterial communities to a cadmium pollution gradient - Li Hu; Ru Wang; Xianglin Liu; Bo Xu; Tuanhui Xie; Yunyun Li; Mingkuang Wang; Guo Wang; Yanhui Chen (Environmental Science and Pollution Research, 2018)

Demographic expansion and genetic load of the halophyte model plant Eutrema salsugineum - Xiao‐Juan Wang; Quan‐Jun Hu; Xin‐Yi Guo; Kun Wang; Da‐Fu Ru; Dmitry A. German; Elizabeth A. Weretilnyk; Richard J. Abbott; Martin Lascoux; Jian‐quan Liu (Molecular Ecology, 2018)
The halophyte model plant Eutrema salsugineum (Brassicaceae) disjunctly occurs in temperate to subarctic Asia and North America. This vast, yet extremely discontinuous distribution constitutes an ideal system to examine long‐distance dispersal and the ensuing accumulation of deleterious mutations as expected in expanding populations of selfing plants. In this study, we resequenced individuals from 23 populations across the range of E . salsugineum . Our population genomic data indicate that E . salsugineum migrated “out of the Altai region” at least three times to colonize northern China, northeast Russia and western China. It then expanded its distribution into North America independently from northeast Russia and northern China, respectively. The species colonized northern China around 33.7 thousand years ago (kya) and underwent a considerable expansion in range size approximately 7–8 kya. The western China lineage is likely a hybrid derivative of the northern China and Altai lineages, originating approximately 25–30 kya. Deleterious alleles accumulated in a stepwise manner from (a) Altai to northern China and North America and (b) Altai to northeast Russia and North America. In summary, E . salsugineum dispersed from Asia to North America and deleterious mutations accumulated in a stepwise manner during the expansion of the species’ distribution.

Brain MRI findings in acute hepatic encephalopathy in liver transplant recipients - Ruo-Mi Guo; Qing-Ling Li; Li-Ru Zhong; Yu Guo; Ju Jiao; Shao-Qiong Chen; Jin Wang; Yong Zhang (Acta Neurologica Belgica, 2018)

Over-expression of the Arabidopsis formate dehydrogenase in chloroplasts enhances formaldehyde uptake and metabolism in transgenic tobacco leaves - Ru Wang; Zhidong Zeng; Hongxia Guo; Hao Tan; Ang Liu; Yan Zhao; Limei Chen (Planta, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

Impacts of climate variability and changes on domestic water use in the Yellow River Basin of China - Xiao-jun Wang; Jian-yun Zhang; Shahid Shamsuddin; Ru-lin Oyang; Tie-sheng Guan; Jian-guo Xue; Xu Zhang (Mitigation and Adaptation Strategies for Global Change, 2017)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

The regulatory role of silicon on carbohydrate metabolism in Cucumis sativus L. under salt stress - Yongxing Zhu; Jia Guo; Ru Feng; Jianhua Jia; Weihua Han; Haijun Gong (Plant and Soil, 2016)

Ordovician volcano–sedimentary iron deposits of the Eastern Tianshan area, Northwest China: the Tianhu example - Chang-Zhi Wu; Ru-Xiong Lei; M. Santosh; Guo-Xiang Chi; Lian-Xing Gu; Si-Wen Xie (International Geology Review, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

Study on effects of endophytes on growth and production of Z-Ligustilide and ferulic acid in Angelica sinensis - Xin-Guo Zhang; Xiao-Ru Li; Qiang-Lin Wang; Wen-Na Wang; Xiao-Qian Chen (Brazilian Journal of Botany, 2016)

Pertrogenesis and tectonic implications of the late Jurassic basic rocks from the northern Shi‐Hang zone, Southeast China - Qing Zhou; Yao–hui Jiang; Shi–yong Liao; Peng Zhao; Ru–ya Jia; Zheng Liu; Guo–chang Wang; Chun–yu Ni (Island Arc, 2016)
The tectonic setting of the late mesozoic of South China is in a debate between two schools of thought: an intra‐continental rift zone along a passive continental margin or active rifting associated with subduction of the paleo‐Pacific Plate. In this study, we present new sensitive high‐resolution ion microprobe (SHRIMP) U‐Pb zircon ages, along with geochemical data of three basic dikes that cross‐cut the Dexing porphyry copper deposit. The deposit is the largest of its kind in eastern China and part of large scale mineralization associated with Mesozoic magmatic activity in the area. Our results indicate that the dikes were emplaced in the Late Jurassic with an average U‐Pb age of 153.5 ± 2.4 Ma. The intrusions have bulk ε Nd (t) of ca +0.7 and zircon ε Hf (t) value of +1.54 to +6.92. Based on relatively enriched light rare earth elements (LREE) and depleted high‐field‐strength elements (HFSE) abundances with pronounced negative Ta–Nb, Hf–Zr and Ti anomalies in multi‐element diagrams, we propose that these dikes were derived from a subduction‐modified lithospheric mantle source. The variability in Hf isotopes identifies some degree of crustal contaminations. Our data support a scenario with a back‐arc extensional setting or an intra‐arc rift environment associated with the westward subduction of the paleo‐Pacific Plate at or prior to the late Jurassic as the most likely cause for these subduction signatures.

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Silencing of dehydrin CaDHN1 diminishes tolerance to multiple abiotic stresses in Capsicum annuum L. - Ru-gang Chen; Hua Jing; Wei-li Guo; Shu-Bin Wang; Fang Ma; Bao-Gui Pan; Zhen-Hui Gong (Plant Cell Reports, 2015)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Geochronological and geochemical constraints on the petrogenesis and geodynamic setting of the Qianlishan granitic pluton, Southeast China - Chun-Li Guo; Ru-Cheng Wang; Shun-Da Yuan; Sheng-Hua Wu; Bing Yin (Mineralogy and Petrology, 2015)

Augmenter of liver regeneration plays a protective role against hydrogen peroxide-induced oxidative stress in renal proximal tubule cells - Ning Xia; Ru-yu Yan; Qi Liu; Xiao-hui Liao; Hang Sun; Hui Guo; Ling Zhang (Apoptosis, 2015)

System‐wide characterization of bZIP transcription factor proteins involved in infection‐related morphogenesis of M agnaporthe oryzae - Wei Tang; Yanyan Ru; Li Hong; Qian Zhu; Rongfang Zuo; Xianxian Guo; Jingzhen Wang; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2015)
Summary The basic leucine zipper ( bZIP ) domain‐containing transcription factors ( TFs ) function as key regulators of cellular growth and differentiation in eukaryotic organisms including fungi. We have previously identified MoAp 1 and MoAtf 1 as bZIP TFs in M agnaporthe oryzae and demonstrated that they regulate the oxidative stress response and are critical in conidiogenesis and pathogenicity. Studies of bZIP proteins could provide a novel strategy for controlling rice blast, but a systematic examination of the bZIP proteins has not been carried out. Here, we identified 19 additional bZIP TFs and characterized their functions. We found that the majority of these TFs exhibit active functions, most notably, in conidiogenesis. We showed that MoHac 1 regulates the endoplasmic reticulum stress response through a conserved unfolded protein response pathway, MoMetR controls amino acid metabolism to govern growth and differentiation, and MoBzip 10 governs appressorium function and invasive hyphal growth. Moreover, MoBzip 5 participates in appressorium formation through a pathway distinct from that MoBzip 10, and MoMeaB appears to exert a regulatory role through nutrient uptake and nitrogen utilization. Collectively, our results provide insights into shared and specific functions associated with each of these TFs and link the regulatory roles to the fungal growth, conidiation, appressorium formation, host penetration and pathogenicity.

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Nutrients and non-volatile taste compounds in Chinese mitten crab by-products - Yan-Ru Guo; Sai-Qi Gu; Xi-Chang Wang; Ke-Jin Zhuang; Shuai Wang; Jing Shi (Fisheries Science, 2015)

Gene order rearrangement of the M gene in the rabies virus leads to slower replication - Xian-Feng Yang; Jiao-Jiao Peng; Hong-Ru Liang; You-Tian Yang; Yi-Fei Wang; Xiao-Wei Wu; Jiao-Jiao Pan; Yong-Wen Luo; Xiao-Feng Guo (VirusDisease, 2014)

Cloning and characterisation of a pepper aquaporin, CaAQP, which reduces chilling stress in transgenic tobacco plants - Yan-Xu Yin; Wei-Li Guo; Ying-Li Zhang; Jiao-Jiao Ji; Huai-Juan Xiao; Fei Yan; Yan-Yan Zhao; Wen-Chao Zhu; Ru-Gang Chen; Wei-Guo Chai; Zhen-Hui Gong (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

An Emerging Water Contaminant, Semicarbazide, Exerts an Anti-estrogenic Effect in Zebrafish (Danio rerio) - Su Gao; Wei Wang; Hua Tian; Xiaona Zhang; Linlin Guo; Shaoguo Ru (Bulletin of Environmental Contamination and Toxicology, 2014)

Comparison of fatty acid and amino acid profiles of steamed Chinese mitten crab - Yan-Ru Guo; Sai-Qi Gu; Xi-Chang Wang; Lin-Min Zhao; Jin-Yuan Zheng (Fisheries Science, 2014)

Origin of Middle Cambrian and Late Silurian potassic granitoids from the western Kunlun orogen, northwest China: a magmatic response to the Proto-Tethys evolution - Zheng Liu; Yao-Hui Jiang; Ru-Ya Jia; Peng Zhao; Qing Zhou; Guo-Chang Wang; Chun-Yu Ni (Mineralogy and Petrology, 2014)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

A platform for soybean molecular breeding: the utilization of core collections for food security - Li-Juan Qiu; Li-Li Xing; Yong Guo; Jun Wang; Scott A. Jackson; Ru-Zhen Chang (Plant Molecular Biology, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Edaravone Ameliorates Oxidative Damage Associated with Aβ25-35 Treatment in PC12 Cells - Gui-lian Zhang; Wang-gang Zhang; Yun Du; Li Yao; Hong Sun; Ru Zhang; Enqi Liu; Ning Bu; Hai-qin Wu; Lei Zhang; Ting-ting Li; Ying-ying Guo (Journal of Molecular Neuroscience, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Mantle origin of the Dexing porphyry copper deposit, SE China - Qing Zhou; Yao-Hui Jiang; Hui-Hua Zhang; Shi-Yong Liao; Guo-Dong Jin; Peng Zhao; Ru-Ya Jia; Zheng Liu (International Geology Review, 2013)

Increased α-tocotrienol content in seeds of transgenic rice overexpressing Arabidopsis γ-tocopherol methyltransferase - Gui-Yun Zhang; Ru-Ru Liu; Geng Xu; Peng Zhang; Yin Li; Ke-Xuan Tang; Guo-Hua Liang; Qiao-Quan Liu (Transgenic Research, 2013)

A simple method to prepare magnetic modified beer yeast and its application for cationic dye adsorption - Jun-Xia Yu; Li-Yan Wang; Ru-An Chi; Yue-Fei Zhang; Zhi-Gao Xu; Jia Guo (Environmental Science and Pollution Research, 2013)

Characterization and molecular mapping of RsrR, a resistant gene to maize head smut - W. H. Li; X. D. Xu; G. Li; L. Q. Guo; S. W. Wu; Y. Jiang; H. Y. Dong; M. L. Weng; D. M. Jin; J. Y. Wu; Z. G. Ru; B. Wang (Euphytica, 2012)
Maize head smut (MHS) caused by the fungi Sporisorium reilianum (Kühn) Landon and Fullerton ( S. reilianum ) is the most serious disease occurred in China recently. There are only a few reports concerning the genetics of this disease and the resistant gene of maize. In this paper a new dominant resistant gene to MHS caused by the pathogen Shenyang-1 of S. reilianum was discovered from a newly developed resistant inbred line ‘R24’ and was named RsrR. RsrR gene was molecular tagged and mapped on the long arm of maize chromosome 1 via simple sequence repeat-bulked segregant analysis (SSR-BSA) and sequence related amplified polymorphism (SRAP)-BSA analysis, the nearest linkage marker is 2.5 cM apart from the RsrR gene. The gene RsrR has been transferred into two elite maize inbred lines, ‘Huangzao4’ and ‘Qi319’, through traditional hybridization and marker assisted selection. The converted lines can be used in maize MHS-resistance breeding.

Sequence and phylogenetic analysis of H7N3 avian influenza viruses isolated from poultry in China in 2011 - Wu Hai-bo; Lu Ru-feng; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Xu Li-hua; Wu Nan-ping; Guo Chao-tan (Archives of Virology, 2012)

Genetic surface-display of methyl parathion hydrolase on Yarrowia lipolytica for removal of methyl parathion in water - Xing-Xing Wang; Zhe Chi; Shao-Guo Ru; Zhen-Ming Chi (Biodegradation, 2012)

Chemical composition and insecticidal activity of the essential oil of Amethystea caerulea L. - Sha Sha Chu; Quan Ru Liu; Guo Hua Jiang; Zhi Long Liu (Natural Product Research, 2012)

Genetic characterization of subtype H1 avian influenza viruses isolated from live poultry markets in Zhejiang Province, China, in 2011 - Hai-bo Wu; Chao-tan Guo; Ru-feng Lu; Li-hua Xu; En-kang Wo; Jin-biao You; Yi-ting Wang; Qiao-gang Wang; Nan-ping Wu (Virus Genes, 2012)

Characterization of a highly pathogenic H5N1 avian influenza virus isolated from ducks in Eastern China in 2011 - Wu Hai-bo; Guo Chao-tan; Lu Ru-feng; Xu Li-hua; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Wu Nan-ping (Archives of Virology, 2012)

Sociodemographic characteristics and risk factor analysis of Demodex infestation (Acari: Demodicidae) - Ya-e Zhao; Na Guo; Meng Xun; Ji-ru Xu; Mei Wang; Duo-lao Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Long-term (1998–2007) trends on the spatial distribution of heterotrophic ciliates in the East China Sea in summer: effect of the Three Gorges Dam construction - An-Yi Tsai; Gwo-Ching Gong; Kuo-Ping Chiang; Chien-Fu Chao; Herng-Ru Guo (Journal of Oceanography, 2011)

Study of prestack elastic parameter consistency inversion methods - Han-Dong Huang; Ru-Wei Zhang; Guo-Qiang Shen; Fei Guo; Jia-Bei Wang (Applied Geophysics, 2011)

Impacts of erucic acid and glucosinolate content on genetic relationships between protein content and fatty acids of rape seed across environments - Chun-Hai Shi; Wei-Dong Xu; Qian-Ru Yu; Hai-Zhen Zhang; Zhong-Wei Yang; Jian-Guo Wu (Euphytica, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

A phylogeny of Photinia sensu lato (Rosaceae) and related genera based on nrITS and cpDNA analysis - Wei Guo; Yi Yu; Ru-jiang Shen; Wen-bo Liao; Siew-wai Chin; Daniel Potter (Plant Systematics and Evolution, 2011)

Genetic relationships between resistances to Fusarium head blight and crown rot in bread wheat (Triticum aestivum L.) - Hao Bing Li; Guo Qiang Xie; Jun Ma; Gui Ru Liu; Shu Min Wen; Tomohiro Ban; Sukumar Chakraborty; Chun Ji Liu (Theoretical and Applied Genetics, 2010)

Detection of circulating tumor cells in peripheral blood from patients with gastric cancer using microRNA as a marker - Hui Zhou; Jun-Ming Guo; Yan-Ru Lou; Xin-Jun Zhang; Fa-De Zhong; Zhen Jiang; Jia Cheng; Bing-Xiu Xiao (Journal of Molecular Medicine, 2010)

Overexpression of soybean ubiquitin-conjugating enzyme gene GmUBC2 confers enhanced drought and salt tolerance through modulating abiotic stress-responsive gene expression in Arabidopsis - Guo-An Zhou; Ru-Zhen Chang; Li-Juan Qiu (Plant Molecular Biology, 2010)

Biotreatment of oily wastewater by rhamnolipids in aerated active sludge system - Hong-zi Zhang; Xu-wei Long; Ru-yi Sha; Guo-liang Zhang; Qin Meng (Journal of Zhejiang University-SCIENCE B, 2009)

Genetic Diversity and Population Structure of Celosia argentea and Related Species Revealed by SRAP - Na Feng; Qie Xue; Qinghua Guo; Ru Zhao; Meili Guo (Biochemical Genetics, 2009)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

Studies on the factors affecting the growth and hemolytic activity of Anabaena variabilis - Wei Wang; Xiu-Kai Song; Shao-Guo Ru (Journal of Applied Phycology, 2007)

Long-term aerobic exercise protects the heart against ischemia/reperfusion injury via PI3 kinase-dependent and Akt-mediated mechanism - Kun-Ru Zhang; Hai-Tao Liu; Hai-Feng Zhang; Quan-Jiang Zhang; Qiu-Xia Li; Qiu-Jun Yu; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2007)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Hypoxic postconditioning enhances the survival and inhibits apoptosis of cardiomyocytes following reoxygenation: role of peroxynitrite formation - Hai-Chang Wang; Hai-Feng Zhang; Wen-Yi Guo; Hui Su; Kun-Ru Zhang; Qiu-Xia Li; Wenli Yan; Xin L. Ma; Bernard L. Lopez; Theodore A. Christopher; Feng Gao (Apoptosis, 2006)

TransgenicLycium barbarum L. Established as HIV capsid protein expression system - Guo-Li Du; Chang-Zheng Song; Geng-Lin Zhang; Xiao-Guang Sun; Dan-Ru Liu (Plant Molecular Biology Reporter, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Distribution of mercury in typical wetland plants in the Sanjiang plain - Ru-hai Liu; Qi-chao Wang; Yan Wang; Lei Zhang; Zhi-guo Shao (Chinese Geographical Science, 2003)